PENGARUH MOTIVASI KEIKUTSERTAAN DALAM KOMUNITAS BELAJAR TERHADAP PROFESIONALISME DAN KOMPETENSI PEDAGOGIK GURU IPS - Timing Merawati; Bambang Sigit Widodo; Harmanto Harmanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Improving the quality of education is closely related to teacher professionalism and pedagogical competence as the main actors in the learning process. Teacher learning communities have been recognized as a collaborative strategy that can support teachers’ professional development through sharing experiences, reflective discussions, and collaborative learning activities. However, the participation of social studies teachers in teacher learning communities in Cluster 07 of Tangerang Regency remains relatively low, which may affect the quality of instructional practices. This study aims to analyze the influence of teachers’ participation motivation in learning communities on teacher professionalism and pedagogical competence, while also examining the role of active participation as a mediating variable and principal support as a moderating variable. This research employed a quantitative approach using a survey method. The population consisted of 83 social studies teachers who were members of the Social Studies Teacher Learning Community in Cluster 07, Tangerang Regency. A sample of 70 teachers was selected using proportional random sampling. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that teachers’ participation motivation has a positive and significant effect on teacher professionalism and pedagogical competence. Furthermore, motivation also significantly influences professionalism and pedagogical competence through teachers’ active participation in the learning community, indicating that active participation acts as a mediating variable. However, principal support was not found to moderate the relationship between motivation and teachers’ active participation. These findings suggest that improvements in teacher professionalism and pedagogical competence are more strongly influenced by internal factors, particularly teachers’ motivation and their active engagement in learning communities. ABSTRAK Peningkatan mutu pendidikan sangat dipengaruhi oleh profesionalisme dan kompetensi pedagogik guru sebagai pelaksana utama proses pembelajaran. Komunitas belajar guru menjadi salah satu strategi kolaboratif yang dapat mendorong pengembangan profesional guru melalui kegiatan berbagi pengalaman, refleksi pembelajaran, dan kolaborasi antarpendidik. Namun, tingkat partisipasi guru IPS dalam komunitas belajar di Gugus 07 Kabupaten Tangerang masih relatif rendah sehingga berdampak pada belum optimalnya kualitas pembelajaran. Penelitian ini bertujuan untuk menganalisis pengaruh motivasi keikutsertaan guru dalam komunitas belajar terhadap profesionalisme dan kompetensi pedagogik guru IPS, dengan mempertimbangkan peran partisipasi aktif sebagai variabel mediasi serta dukungan kepala sekolah sebagai variabel moderasi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi penelitian berjumlah 83 guru IPS yang tergabung dalam Komunitas Belajar Guru IPS Gugus 07 Kabupaten Tangerang. Sampel penelitian sebanyak 70 guru yang ditentukan menggunakan teknik proportional random sampling. Pengumpulan data dilakukan melalui angket dengan skala Likert dan dianalisis menggunakan metode Partial Least Squares–Structural Equation Modeling (PLS-SEM) dengan bantuan perangkat lunak SmartPLS. Hasil penelitian menunjukkan bahwa motivasi keikutsertaan guru berpengaruh positif dan signifikan terhadap profesionalisme dan kompetensi pedagogik guru. Selain itu, motivasi juga berpengaruh signifikan terhadap profesionalisme dan kompetensi pedagogik melalui partisipasi aktif guru dalam komunitas belajar, sehingga partisipasi aktif berperan sebagai variabel mediasi. Namun demikian, dukungan kepala sekolah tidak terbukti memoderasi hubungan antara motivasi dan partisipasi aktif guru. Temuan ini menunjukkan bahwa peningkatan profesionalisme dan kompetensi pedagogik guru lebih dipengaruhi oleh faktor internal berupa motivasi dan keterlibatan aktif guru dalam komunitas belajar.